STUDY OF THE ELEMENTAL COMPOSITION OF FILLERS OF IRRADIATED POLYMERIC COMPOSITE BY THE METHOD OF X-RAY FLUORESCENCE ANALYSIS - Baimolda, D.; Cechak, T.; Tlebaev, K. B. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
The article studies the elemental composition of the fillers (polytetrafluoroethylene and carbon nanopowder) of the polymer composite depending on various concentrations of fillers and electron irradiation and modified polytetrafluoroethylene (PTFE). The elemental composition of the fillers and their distribution over the depth of the polymer composite and modified polytetrafluoroethylene were studied by X-ray fluorescence analysis (XRFA) and confocal micro-X-ray analysis. X-ray spectra of the polymer composite and modified polytetrafluoroethylene were obtained. It has been established that an increase in the concentration of one component and an irradiation dose leads to a weakening of the intensities of the spectra of the polymer composite and modified polytetrafluoroethylene.